The Role of Asynchronous in Improving Student Achievement - Baron, Gregory; Lorenzo, Courtois; Benoit, Dubois (World Psychology, 2023)
The Covid-19 pandemic has had a huge impact on the world of education. The learning process is usually carried out face-to-face, but during the Covid-19 pandemic, schools were required to follow government policies regulated by the Ministry of Education and Culture. Where the learning process is carried out in asynchronous learning, so that a teacher is highly demanded to be able to use interesting learning media, create a creative and innovative learning atmosphere so that students can understand learning material easily. Asynchronous is a learning system that is carried out delayed or indirectly, so that the teacher can only provide knowledge not in educating the student's character. However, students can easily access learning materials anytime and anywhere. This research was conducted aiming to describe the role of asynchronous in improving student achievement. This research uses quantitative methods using survey models, google forms and in-depth interviews. The results of this study indicate that student achievement will increase if these students are able to make good use of the asynchronous system in the learning process. The limitation of this study is that researchers have difficulty knowing student learning progress by using an asynchronous system in improving student achievement. Therefore, it is hoped that future researchers will be more thorough in reviewing student achievement using an asynchronous system.